2015
DOI: 10.1117/12.2177527
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chemical clouds using widely tunable quantum cascade lasers

Abstract: Widely tunable quantum cascade lasers (QCLs) spanning the long-wave infrared (LWIR) atmospheric transmission window and an HgCdTe detector were incorporated into a transceiver having a 50-mm-diameter transmit/receive aperture. The transceiver was used in combination with a 50-mm-diameter hollow retro-reflector for the open-path detection of chemical clouds. Two rapidly tunable external-cavity QCLs spanned the wavelength range of 7.5 to 12.8 m. Open-path transmission measurements were made over round-trip path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, standoff measurements using dual frequency comb spectroscopy at 3.03-3.64 µm for the detection of broadband-absorbing species acetone and isopropanol reported sensitivities of 2-6 ppm × m but required a long 60 s averaging time [50]. For standoff detection using other LWIR ECQCL systems, Goyal et al reported a NECD for Freon-134a of 1 ppm × m at a 5 s averaging time and 155 m standoff distance [17]; F152a and SF 6 were also detected, but NECD values were not provided. An active coherent laser spectrometer (ACLaS) system using a broadly tunable ECQCL scanned in 30 s was used to measure Freon-134a in a diffuse reflection standoff mode at 3 m, reporting a NECD of 10.5 ppm × m Hz −1/2 [15].…”
Section: Characterization Of Performance For Swept-ecqcl and Hyperspe...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, standoff measurements using dual frequency comb spectroscopy at 3.03-3.64 µm for the detection of broadband-absorbing species acetone and isopropanol reported sensitivities of 2-6 ppm × m but required a long 60 s averaging time [50]. For standoff detection using other LWIR ECQCL systems, Goyal et al reported a NECD for Freon-134a of 1 ppm × m at a 5 s averaging time and 155 m standoff distance [17]; F152a and SF 6 were also detected, but NECD values were not provided. An active coherent laser spectrometer (ACLaS) system using a broadly tunable ECQCL scanned in 30 s was used to measure Freon-134a in a diffuse reflection standoff mode at 3 m, reporting a NECD of 10.5 ppm × m Hz −1/2 [15].…”
Section: Characterization Of Performance For Swept-ecqcl and Hyperspe...mentioning
confidence: 99%
“…Standoff optical-based measurement over a discrete line-of-sight provides enhanced spatial coverage, including the detection of plumes aloft, and may operate continuously in time. Sensors based on infrared spectroscopy to measure path-integrated chemical concentrations may use thermal (incoherent) sources, such as open-path Fourier transform infrared (OP-FTIR) [10][11][12][13], or may use active laser-based sources [14][15][16][17][18][19][20][21]. Laser-based sensors may operate in a LIDAR configuration to provide range-resolved or integrated column information [22][23][24] and can provide useful spatial and depth information for plume measurements in some cases, but only if sufficient backscatter from aerosol particles is available [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is almost no extra loss in detection capability compared with the latter, due to the use of optical reflectors. A broadly-tunable ECQCL operating at 20 Hz spectral sweep rate and spectral resolution of 4 cm −1 was used for standoff gas-phase chemical detection over 300-600 m distances using a corner-cube retroreflector, from which noise equivalent concentration length (NECL) values as low as 0.75 ppm•m in 2-5 s averaging times were estimated for strongly absorbing chemicals [90]. The main application scenarios include measurement of greenhouse gas emissions [91], hazardous gas detection in underground coal mines [92], atmospheric composition monitoring [93][94][95], leak detection in petroleum storage tanks [87], standoff detection of alcohol vapors exhaled by humans [96], etc.…”
Section: Tdlas With Retroreflectorsmentioning
confidence: 99%
“…If a threat cloud crosses the "optical fence", the LaserWarn system will detect its presence. In addition to sequentially interrogating multiple-beam paths, it is also practicable to configure a system of mirrors such that the laser beam crisscrosses the facility in such a way that the transceiver does not require to move [90]. Moreover, the LaserWarn system is suitable for the protection of large indoor areas, such as airports.…”
Section: Tdlas With Retroreflectorsmentioning
confidence: 99%